Pendampingan Petani Padi Melalui KKN Pembelajaran Pemberdayaan Masyarakat Desa Piasa Kulon Kabupaten Banyumas - Ahadiyat Yugi Rahayu; Okti Herliana; Sapto Nugroho Hadi; Ida Widiyawati (Jurnal Ilmiah Pangabdhi, 2021)
The Ngudi Mratani Farmers Group in Piasa Kulon Village is one of the producers of healthy rice that is cultivated organically, but there are several obstacles in providing fertilizers, biopesticides and marketing the rice produced. The objectives of this activity are 1) providing technology transfer in organic rice cultivation by utilizing rabbit urinee as liquid organic fertilizer (POC) 2) Providing training on the manufacture of Local Micro Organisms (MOL) and biopesticides 3) providing assistance related to marketing organic rice. This activity was carried out in July - August 2017 by KKN-PPM students of Jenderal Soedirman University accompanied by a team of service providers from the Faculty of Agriculture as field supervisors. The method used is Rural Appraisal Participation (PRA), which is the active involvement of all parties involved in activities. The stages of the activity were direct field surveys, interviews, training discussions and mentoring on organic rice cultivation techniques, post-harvest handling and marketing. The results of this activity were an increase in farmer understanding by 35%, farmer skills in making MOL, POC rabbit urinee and vegetable pesticides to support organic rice production by 50%. The existence of attractive post-harvest handling and product packaging that increases the quality and selling power of the organic rice produced.